Hashimoto Thyroiditis in Primary Thyroid Non-Hodgkin Lymphoma: A Systematic Review and Meta-Analysis. Issue 2 (4th October 2019) - Travaglino, Antonio; Pace, Mirella; Varricchio, Silvia; Insabato, Luigi; Giordano, Claudia; Picardi, Marco; Pane, Fabrizio; Staibano, Stefania; Mascolo, Massimo
Abstract: Objectives: To assess the prevalence of Hashimoto thyroiditis (HT) in primary thyroid lymphoma (PTL) and whether it differs between mucosa-associated lymphoid tissue (MALT) lymphoma and diffuse large B-cell lymphoma (DLBCL). Methods: Electronic databases were searched for studies assessing HT prevalence in PTL, based on antithyroid antibodies, clinical history, or pathology. Pooled prevalence of HT and its association with histotype (MALT or DLBCL) were calculated. Results: Thirty-eight studies with 1, 346 PTLs were included. Pooled prevalence results were 78.9% (any HT evidence), 65.3% (antithyroid antibodies), 41.7% (clinical history), and 64% (pathology). HT prevalence was significantly higher in MALT lymphoma than in DLBCL ( P = .007) and in mixed DLBCL/MALT than in pure DLBCL ( P = .002). Conclusions: Overall, 78.9% of patients with PTL have any HT evidence, but only half of these had been clinically followed. The difference in HT prevalence suggests that a subset of DLBCL may not derive from MALT lymphoma.